Enhanced flash droughts in recent decades over the Arabian Peninsula - Md Saquib Saharwardi; Waqar Ul Hassan; Hari Prasad Dasari; Yasser Abualnaja; Ibrahim Hoteit (Journal of Hydrology: Regional Studies)
Study region: Arabian Peninsula (AP) is an arid region with less rainfall and high temperature throughout the year. Study focus: Flash droughts have emerged as a significant threat to water resources and ecosystems globally. Despite the far-reaching consequences of flash droughts, their spatiotemporal variability remains uncertain, especially in arid regions including the AP. This study analyzes the evolution and characteristics of flash droughts in the AP from 1981 to 2022, using the root zone soil moisture (RZSM) data. New hydrological insight: Our findings reveal a significant increasing trend in frequency and duration of flash drought with ∼32 % increase in area-affected in the AP during the last two decades (2002–2022) compared to the previous decades (1981–2001). This escalation is mainly attributed to the rainfall reduction and amplified warming that has been observed across the region. In particular, the northern regions experience more frequent flash droughts (∼70 %) than the southern regions during winter, and this pattern reverses during summer. We observed that rainfall has a stronger influence on flash droughts due to soil-moisture depletion than potential-evaporation. In general, a higher number of flash droughts is observed during winter, however, the mean duration of droughts is longer in summer. Interestingly, the RZSM percentile nearly reaches zero during summer flash drought compared to winter. The occurrence of severe and widespread flash droughts indicates serious concern for the AP region.